Visionary Leadership in Managing BUM Desa - RIFA'I, AHMAD; Widyanto, Irfan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This article aims to formulate things that need to be done and describe the visionary leadership model in managing BUM Desa. This is important to do to provide a comprehensive understanding of visionary leadership in managing BUM Desa. Methodology/approaches – The research method used in writing this article is a literature review method from various sources related to visionary leadership in managing BUM Desa. Findings – It The results of this literature review illustrate that there are 5 leadership perspectives, namely: Competency perspective, Behavioral perspective, Contingency perspective, Transformational perspective, Implicit leadership perspective. Visionary leadership positions are sharpening from a transformational perspective. There are 5 dimensions of visionary leadership: Challenge the process, be enthusiastic, help others to act, set the example, celebrate achievement. Novelty/values – The research succeeded in formulating things that need to be done by operational implementers in managing BUM Desa using visionary leadership